(untitled) (Research, Society and Development, 2022)
Objective: to identify scientific evidence in the literature on the use of pequi oil (Caryocar brasiliense) in the wound healing process. Method: Integrative literature review carried out in MEDLINE, EBSCO, LILACS, considering as criteria for inclusion publications available online; in English, Portuguese or Spanish, published between 2015 and 2022; and that addressed the use of pequi oil extract in wound healing. Review articles, duplicates, unrelated to the theme, and gray publications were excluded. After selecting the studies, the selected articles were analyzed and synthesized. Results: Three articles were included, 100% of which were randomized controlled trials, in 2015 (66.7%). Conclusion: pequi oil has a beneficial action in the tissue repair process of wounds in rats, evidenced by the reduction of the inflammatory response and greater collagen deposition, increasing the healing speed.